Hubungan Pemahaman Nilai-Nilai Ketuhanan Yang Maha Esa Pada Pelajaran PPKN Dengan Sikap Religius Siswa Kelas VIII SMP Negeri 17 Kota Jambi - Suci; Irzal; Sariani, Dona (Civic Education Perspective Journal, 2021)
Abstract: This study aims to determine the relationship between understanding the values ​​of God Almighty and the religious attitudes of eighth grade students of SMP Negeri 17 Jambi City. This research is a quantitative descriptive study using the correlational method carried out at SMP Negeri 17 Jambi City in class VIII students with a sample of 61 people. The data in this study were collected through a questionnaire, processed by a simple correlation test using a t-test with Microsoft Excel 2010 and SPSS version 24. Based on the results of the study, it shows that there is a relationship between understanding the values ​​of the One Supreme God and religious attitudes. Calculation of the coefficient r_xy calculate the correlation value of 0.437 or in the moderate category and the t-test is significant, the value is t_count = 3.728 > t_table = 1.670. Based on the results of the study, it can be concluded that there is a significant relationship between the data on understanding the values ​​of the Almighty God and the religious attitudes of eighth grade students of SMP Negeri 17 Jambi City.